IoT & Cloud Based Attendance Collection and Student Information Chatbot - Perera, L.A.; Tharuka Ravishan; Welhenge, Anuradhi (2022)
The system proposed in this paper addresses two main concerns in the higher education system. One is efficient attendance monitoring of students, and the other concern is implementing an effective mechanism to interact with students to clarify their issues. As for the first concern, an IOT based attendance collection system will be proposed and for the second concern a cloud based chatbot is proposed. The main purpose of the proposed attendance collection system is to provide more efficient methodology to both students and lecturers while eliminating frequent issues such as buddy signing, loss of attendance sheets while improving student attendance scores. There are two parts to the attendance collection system. One is an IOT based device with biometric authentication for attendance collection which was developed using Arduino, microcontrollers, and fingerprint sensors. Second part is a web-based attendance system designed for lecturers or administrators for report generation, which was developed using Structured Query Language (SQL), PHP, JavaScript and HTML. The generated reports can be converted into excel or PDF files as required. As students are more familiar with smart devices than ever, a student information chatbot is proposed as a mechanism to interact with students to clarify their issues. The system establishes transparent and efficient communications with students for their general questions. The prototype chatbot was implemented in google cloud infrastructure and it is integrated with an android application which was built using android studio. The application can be used to interact with the chatbot and have the scalability for more features in the future.